2017
DOI: 10.1108/ijsms-08-2017-093
|View full text |Cite
|
Sign up to set email alerts
|

Sport fans in a “smart sport” (SS) age: drivers of smartphone use for sport consumption

Abstract: Purpose With the ever-increasing popularity of smartphones, it has become one of the most important medium to increase sport fan engagement. However, very little attention has been paid to understand how fans use smartphones to follow sport. With that in mind, the purpose of this paper is to investigate specific factors that influence the use of smartphones in the sport consumption context. Design/methodology/approach This research empirically examined theoretical relationships between three categories of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 46 publications
1
51
0
1
Order By: Relevance
“…These results have contributed to a gap that existed in the academic literature on the history of the use of fitness Apps. In fact, authors such as Ha et al [ 50 ] showed that there were no research works that had investigated the factors or behaviors that conducted sports consumers to use sports Apps. Thus, as with previous authors [ 27 , 37 , 57 ], this study’s findings have shown that the use intentions of fitness Apps could be conditioned initially by e-lifestyles and that perceived ease of use and the perceived usefulness would mediate the attitudes and intentions of using Fitness Apps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results have contributed to a gap that existed in the academic literature on the history of the use of fitness Apps. In fact, authors such as Ha et al [ 50 ] showed that there were no research works that had investigated the factors or behaviors that conducted sports consumers to use sports Apps. Thus, as with previous authors [ 27 , 37 , 57 ], this study’s findings have shown that the use intentions of fitness Apps could be conditioned initially by e-lifestyles and that perceived ease of use and the perceived usefulness would mediate the attitudes and intentions of using Fitness Apps.…”
Section: Discussionmentioning
confidence: 99%
“…In the sports sector, there are some studies that have analyzed these variables, finding relationships between PEU and PU [ 49 , 50 ], PEU and PU on the intention of use [ 25 , 49 , 51 ], or the intention of use and the actual use of the App [ 12 ]. Likewise, they have been analyzed in different sport contexts, such as sports websites [ 52 ], fitness Apps [ 49 ], sports products [ 53 ], sport teams Apps [ 51 ], or smartphone use for sports consumption [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the rise of social media platforms in the sports context has enabled professional sports teams to enhance the frequency and intensity of their interactions with their audience [10]. The provision of mobile servicessuch as smartphone apps that provide player statistics and betting functionalityhas become a crucial part of formulating sport marketing strategies and gave several benefits for professional sports teams [11]. Even though individual athletes are relevant assets and investments, professional sports teams need to concentrate their efforts on managing the team's brand [12] and align these efforts with the brands of the individual athletes.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, online games, called eSports, have been officially recognized as new sports in international competitions [6]; additionally, sports broadcasts can be watched around the world without constraints of time or place [7], and purchasing sports-related products has become easier than before [5]. These changes caused by the internet have reached a peak with the release of high-tech devices, such as smartphones [8].…”
Section: Introductionmentioning
confidence: 99%